Public perceptions of responsibility and liability in the licensed drinking environment - Lang, E.; Stockwell, Tim; Rydon, P.; Lockwood, A. (Taylor and Francis, 1993)
This study reports the results of a survey conducted in Perth (Western Australia) to assess public perceptions of the concepts of server responsibility and server liability. Eleven hundred and sixty persons aged 16 and over were asked if they thought licensees and barstaff should be held partly responsible when someone becomes intoxicated on licensed premises, or licensees and barstaff should be partly liable for injuries caused by an intoxicated person after leaving licensed premises. Results indicate that, on average, few people agreed to either proposition, despite an overwhelming majority believing that continuing to serve an intoxicated person increases the risk of an accident. However, when analysed by category of respondent, non-drinkers and persons aged over 30 were significantly more likely to agree with licensees and barstaff being partly responsible for someone becoming intoxicated, and for them to be partly liable in the case of an accident involving an intoxicated customer. The results of this survey indicate the need for education programmes to convince the public that excessive alcohol consumption and the resulting harm is not merely the responsibility of the individuals concerned, but is also the responsibility of those groups and individuals involved in the promotion, marketing and sale of alcohol. We suggest that such education campaigns might best be targeted at those groups where least support was found, young drinkers (18-24 years) and the servers of alcohol.